2019
DOI: 10.3390/v11121108
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Roseoloviruses in Humans, Pigs, Mice, and Other Species

Abstract: Viruses of the genus Roseolovirus belong to the subfamily Betaherpesvirinae, family Herpesviridae. Roseoloviruses have been studied in humans, mice and pigs, but they are likely also present in other species. This is the first comparative analysis of roseoloviruses in humans and animals. The human roseoloviruses human herpesvirus 6A (HHV-6A), 6B (HHV-6B), and 7 (HHV-7) are relatively well characterized. In contrast, little is known about the murine roseolovirus (MRV), also known as murine thymic virus (MTV) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 215 publications
0
50
0
Order By: Relevance
“…Furthermore, the vulnerability of vascular endothelial cells, especially in the case of infection reactivation, is shown in the given study. Available serological data suggest that primary herpesvirus infection occurs early in childhood and results in a lifelong infection [ 24 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the vulnerability of vascular endothelial cells, especially in the case of infection reactivation, is shown in the given study. Available serological data suggest that primary herpesvirus infection occurs early in childhood and results in a lifelong infection [ 24 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…A viral etiology is evident for approximately 1% of all cases of acute arthritis [ 20 ]. Human herpesviruses are ubiquitous pathogens establishing a persistent infection in the host for life, but their contribution to articular damage and the etiopathogenesis of OA remains obscure [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…While CRISPR‐Cas‐9 genome editing can remove the PERV pol gene from pig, the risk of xenozoonosis with other roseoloviruses remains . For example, porcine cytomegalovirus was the cause of a significant reduction of the survival time of the transplanted pig organs .…”
Section: Improving Safety Of the Xenograftmentioning
confidence: 99%
“…HHV-6A infection was shown to accelerate the progression of AIDS (acquired immunodeficiency syndrome) in SIV (simian immunodeficiency virus)-infected macaques [9] and lead to neurological symptoms in marmosets [10]. HHV-6A/B and HHV-7 belong to the genus Roseolovirus of the subfamily Betaherpesvirinae, family Herpesviridae, and they are closely related to the murine roseolovirus (MRV) and the porcine cytomegalovirus/porcine roseolovirus (PCMV/PRV), which are ubiquitous in nature [11].…”
mentioning
confidence: 99%
“…The presence of MRV, also known as the mouse thymic virus (MTV), may influence the results in the murine models. MRV/MTV has been isolated from the brains of mice infected shortly after birth but not of those infected at the adult stage [11,16]. No studies on the impact of MRV on the brain have been reported until now.…”
mentioning
confidence: 99%